Potensi Antibakteri Mouthwash Ekstrak Daun Rambutan (Nephelium Lappaceum L.) Hasil Ultrasonic Assisted Extraction (UAE) dengan Metode Difusi Sumuran terhadap Streptococcus Mutans ATCC 25175 - Faza Rusyda; Riana Putri Rahmawati; Muhammad Nurul Fadel (Universitas Pahlawan Tuanku Tambusai, 2026)
lappaceum leaves (Nephelium lappaceum L.) possess antibacterial, anti-inflammatory, and antioxidant, properties due to the presence of secondary metabolites such as alkaloids, flavonoids, saponins, and tannins, and terpenoids. This study aimed to formulate a mouthwash preparation from rambutan leaf extract and avaluate is antibacterial activity against Streptococcus mutans, in the process of extracting rambutan leaves using 70% ethanol with the UAE method (Ultrasonic Assisted Extraction), rambutan leaf extracts were subjected to phytochemical screening examinations that include flavonoids, saponins, alkaloids, tannins, and terpenoids. The type of research conducted was experimental in the laboratory with the formulation of rambutan leaf extract (Nephelium lappaceum L) in mouthwash preparations using a concentration of 5% for F1, 10% for F2 and 15% for F3, the mouthwash preparations were subjected to physicochemical tests including organoleptic tests of pH, homogeneity, specific gravity, and viscosity. Antibacterial activity testing was carried out using the well diffusion method. The results of the research on the mouthwash formulation from rambutan leaf extract showed good physical organoleptic quality, pH, homogeneity, specific gravity, and viscosity of the preparation. In testing the antibacterial activity of the mouthwash preparation, the inhibition zone value at F0 did not have an inhibition zone; F1 6.92 (moderate) mm; F2 8.83 (moderate) mm; F3 11.00 mm (strong); and positive control 22.73 mm (strong), these results indicate that the higher the extract, the higher the inhibition zone produced.